Dystonia and Cerebellum: From Bench to Bedside - Ryoma Morigaki; Ryosuke Miyamoto; Taku Matsuda; Kazuhisa Miyake; Nobuaki Yamamoto; Yasushi Takagi (Life, 2021)
Dystonia pathogenesis remains unclear; however, findings from basic and clinical research suggest the importance of the interaction between the basal ganglia and cerebellum. After the discovery of disynaptic pathways between the two, much attention has been paid to the cerebellum. Basic research using various dystonia rodent models and clinical studies in dystonia patients continues to provide new pieces of knowledge regarding the role of the cerebellum in dystonia genesis. Herein, we review basic and clinical articles related to dystonia focusing on the cerebellum, and clarify the current understanding of the role of the cerebellum in dystonia pathogenesis. Given the recent evidence providing new hypotheses regarding dystonia pathogenesis, we discuss how the current evidence answers the unsolved clinical questions.